1998
DOI: 10.1159/000054393
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-Dependent Regulation of Galanin Synthesis in Neurons and Glial Cells after Colchicine Administration

Abstract: Galanin and galanin message-associated peptide (GMAP) synthesis is up-regulated in neurons and glial cells in the adult rat brain by different experimental manipulations, including intracerebroventricular colchicine. We have previously reported that the galanin expression is severely attenuated in some neurons in adult hypothyroidism. In order to further investigate the role of thyroid hormone for the in vivo regulation of galanin gene expression, we have studied the effect of intraventricular administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, in a study using icv injections of colchicine, Calza et al [4] demonstrated that colchicine-induced NG2 cell-specific galanin up-regulation did not occur in thyroidectomised, hypothyroid adult rats, although neuronal galanin up-regulation was preserved in some neuronal populations. These data suggest that endogenous thyroid hormone could mediate injury-induced glial galanin production, potentially regulated by a thyroid hormone responsive element in the galanin promoter.…”
Section: Regulation Of Glial Galanin Expression and Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a study using icv injections of colchicine, Calza et al [4] demonstrated that colchicine-induced NG2 cell-specific galanin up-regulation did not occur in thyroidectomised, hypothyroid adult rats, although neuronal galanin up-regulation was preserved in some neuronal populations. These data suggest that endogenous thyroid hormone could mediate injury-induced glial galanin production, potentially regulated by a thyroid hormone responsive element in the galanin promoter.…”
Section: Regulation Of Glial Galanin Expression and Secretionmentioning
confidence: 99%
“…Absence of co-labelling with another microglia/macrophage marker, ED1, confirmed that another glial cell type other than macrophages or microglia was likely to be responsible for trauma-induced galanin expression [4]. Ubink and colleagues [5] subsequently demonstrated that the glial cell type expressing galanin after icv colchicine injection was positive for the cell surface proteoglycan, NG2.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…2002; Barreda‐Gomez et al. 2005) whose expression has been shown to be TH‐regulated (Calza et al. 1998; Kolakowski et al.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired PTP in ganglia from hypothyroid rats reported here is in agreement with an earlier finding in hypothyroid cat ganglia (Pascalov‐Stoenescu and Sterescu, 1971). The mechanism responsible for impairment of PTP in hypothyroid ganglia is unknown, but could be due to decreased de novo synthesis of presynaptic voltage‐operated calcium channels, or other protein molecules involved in transmitter release, resulting from hypothyroidism‐decreased protein synthesis (Wibo et al, 1995; Calza et al, 1998).…”
Section: Discussionmentioning
confidence: 99%